The Effectiveness of Android Based Digital Arithmetic Learning Media with Discovery-Based Learning Model to the Learning Achievement of Computer System Subject of Grade X of Multimedia Class at Vocational High School in Surakarta - Rofifah Nur Mufidah; Agus Efendi; Cucuk W Budiyanto (IJIE (Indonesian Journal of Informatics Education), 2019)
The purpose of this research is to determine (1) the effectiveness of the use of learning media based on android Arithmetic Digital with discovery-based learning model to learning achievement of computer system grade X of multimedia class at vocational high school 6 Surakarta, (2) the differences in students’ achievement between the control class and experimental class were given the action of using Android learning media with discovery-based learning model. The population of this research is students of grade X of Multimedia class at Vocational high school 6 Surakarta. This study uses an experimental quasi-approach. The techniques of data collection in this study using the test method to determine the results of pretest and post-test. The observation method is to know the difference of student activity of control class and experiment class. Data analysis used was non-parametric test by using Mann Whitney test and Wilcoxon rank test.Based on the research, it can be concluded that the Android-based learning media with discovery-based learning model more effective in improving learning achievement compared with the conventional model. This is evidenced by the Wilcoxon sign rank test which gives a result of the significance of 0.000 < 0.005, which means there is a difference in mean values between the two classes. The experimental class got a higher average score that is 84.14 and the control class is 67.59. The result of this research is also reinforced by student gain index analysis, with gain of experimental class that is 0,70 which mean inclination category of high learning achievement while the gain’s improvement of control class is equal to 0,40 which means inclusive category of improvement in learning achievement, this matter because in the model of discovery-based learning able to improve student activeness in learning as well as to develop student's way of learning by finding their own, and self-investigate. And combined with the right learning media such as Android, will increasingly foster student interest in learning.